In-vitro inhibitory effect of EGFL7-RNAi on endothelial angiogenesis in glioma - Li, Qiang (Int J Clin Exp Pathol, 2015)
Objective: To investigate the role and mechanism of epidermal growth factor like domain 7 (EGFL7) in glioma angiogenesis by cell co-culture and RNA interference. Methods: NSCs-HUVECs co-culture system was established using Transwell culturing techniques. The interactions between glioma and endothelial cells were simulated in-vitro. Cellular expression of EGFL7 in NSCs and HUVEC was targeted and suppressed by lentiviral vector carrying siRNA. The effect of EGFL7 on angiogenesis in glioma in-vitro micro-environment was detected by endothelial cell proliferation, adhesion and tube formation assay. Results: Following EGFL7 gene silencing, expression of EGFL7 in HUVECs was reduced and cell adhesion capability was inhibited significantly. Endothelial cells failed to form a lumen-like structure after EGFL7 gene silencing, shown by the tube formation assay. Conclusion: By regulating endothelial cell adhesion, EGFL7 plays a key role in the regulation of glioma angiogenesis.